Environment-friendly anti-aging adhesive and preparation method thereof
By using the combination of specific components and additives in the epoxy resin adhesive to form an interpenetrating and tangled network structure, the problems of epoxy resin adhesive being hard and brittle, poor toughness and insufficient heat-resistant aging performance after curing are solved, and the epoxy resin adhesive is achieved Environmentally friendly, aging-resistant adhesive with good mechanical properties.
Patent Information
- Application Number
- CN202411335236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The existing epoxy resin adhesives have problems such as hardness and brittleness, poor toughness and easy cracking after curing, and have poor heat-resistant aging performance, making it difficult to balance environmental protection, aging resistance and mechanical properties.
Bisphenol A type vinyl ester resin, bisphenol A type liquid epoxy resin and cashew phenol epoxy resin are used as component A, and carboxylated metal organic frames, lignin containing amino and double bonds and SBS as components B. By optimizing the proportion of components and the addition of additives, an interpenetrating and tangled network structure is formed to improve the overall performance of the adhesive.
It has achieved the preparation of environmentally friendly and aging-resistant adhesives, which have good aging resistance, mechanical properties and toughness, and is not easy to crack during use, and meets environmental standards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin adhesives, and specifically discloses an environmentally friendly aging-resistant adhesive and a preparation method thereof. Background Art
[0002] Epoxy resin has excellent properties such as wear resistance, mechanical properties, adhesion, chemical stability, electrical insulation, and adhesion, and is widely used in various fields. Adhesives prepared from epoxy resin have high bonding strength and excellent chemical resistance, but epoxy resin is hard and brittle after curing, has poor toughness and is easy to crack, and has poor heat aging resistance, so it is necessary to modify the epoxy resin.
[0003] The existing technology often improves the heat aging resistance of epoxy resin by adding inorganic fillers, introducing phenolic resins, and introducing heat-resistant structural units into epoxy resin segments. However, some of these modification methods will lead to reduced toughness of epoxy resin, and some cannot meet environmental protection requirements, making it difficult to achieve a balance among environmental protection, aging resistance, and mechanical properties. In summary, it is of great significance to study an environmentally friendly, aging-resistant, and mechanically good adhesive and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide an environmentally friendly aging-resistant adhesive and a preparation method thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solution: an environmentally friendly aging-resistant adhesive, comprising component A and component B; the component A comprises the following raw materials, by mass: 10 to 15 parts of bisphenol A type vinyl ester resin, 45 to 55 parts of bisphenol A type liquid epoxy resin, and 5 to 10 parts of cardanol epoxy resin; The component B comprises the following raw materials, calculated by weight: 15-20 parts of amine curing agent, 12-15 parts of additive A, 3-4 parts of additive B, 0.5-1 parts of additive C, and 0.01-0.02 parts of photoinitiator 1173; The additive A is a metal organic framework loaded with a curing agent; the additive B is lignin containing amino groups and double bonds; the additive C is styrene-butadiene-styrene; and the amine curing agent is 4,4-diaminodiphenyl sulfone; The model of the bisphenol A type vinyl ester resin is 854, the model of the bisphenol A type liquid epoxy resin is E51, and the model of the cardanol epoxy resin is NC-513.
[0006] More optimally, the preparation of the additive A specifically includes the following steps: S1: taking zinc acetate and copper acetate, adding them to water for ultrasonic dispersion, adding pyromellitic acid, stirring to dissolve, adding glacial acetic acid, stirring evenly, condensing and refluxing, centrifuging and washing, drying the substance deposited in the centrifuge tube, adding methanol, activating at 95-100°C for 20-24h, and drying to obtain an intermediate; S2: Take 2-methylimidazole and add it to ethanol, mix it by ultrasonication, add the intermediate, stir it at a constant speed, and remove the ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S3: Take the carboxylated metal organic framework, freeze-dried porous cellulose, terminal hydroxyl silicone oil, and zinc sulfate, add them to a mixed solution of water and ethanol (the volume ratio of water to ethanol is 2:1), mix them evenly, pressurize and heat to 110~120℃ to react for 8~10h, remove the mixed solvent, and obtain additive A.
[0007] More optimally, the intermediate comprises the following raw materials, by weight: 3-4 parts of zinc acetate, 2-3 parts of copper acetate, 100-120 parts of water, 4-6 parts of pyromellitic acid, 65-70 parts of glacial acetic acid, and 100-120 parts of methanol; The carboxylated metal organic framework comprises the following raw materials, calculated by weight: 0.3-0.5 parts of 2-methylimidazole, 100-120 parts of ethanol, and 1-1.5 parts of an intermediate; The additive A comprises the following raw materials, calculated by weight: 12-15 parts of carboxylated metal organic framework, 3-4 parts of freeze-dried porous cellulose, 4-6 parts of terminal hydroxyl silicone oil, 0.1-0.2 parts of zinc sulfate, and 50-60 parts of a mixed solution of water and ethanol.
[0008] More optimally, the preparation of the freeze-dried porous cellulose specifically includes the following steps: taking microfibrillated cellulose and water, ultrasonically dispersing them uniformly, and freeze-drying them to obtain freeze-dried porous cellulose; the mass ratio of microfibrillated cellulose to water is 1: (5~6).
[0009] More optimally, the preparation of the additive B specifically includes the following steps: Step 1: Take lignin, add dichloromethane and triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 2-3 hours, drop acryloyl chloride, stir at 40-45°C for 20-24 hours, add ethanol and stir for 2-3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Step 2: Take modified lignin, polyethylene glycol, and NaOH aqueous solution, stir evenly, add diethylenetriamine dropwise, stir evenly, add formaldehyde aqueous solution dropwise, react at 90-95°C for 3-4h, pour the reaction product into water for precipitation, wash, filter, and dry to obtain additive B.
[0010] More optimally, the modified lignin includes the following raw materials, calculated by weight: 1-2 parts of lignin, 40-60 parts of dichloromethane, 3-6 parts of triethylamine, 10-15 parts of acryloyl chloride, and 10-15 parts of ethanol; The additive B comprises the following raw materials, calculated by weight: 10-15 parts of modified lignin, 2-3 parts of polyethylene glycol, 3-5 parts of diethylenetriamine, and 10-15 parts of formaldehyde aqueous solution with a formaldehyde concentration of 37 wt%; the NaOH aqueous solution comprises 0.01 parts of NaOH and 12 parts of water.
[0011] More optimally, in the styrene-butadiene-styrene, the ratio of styrene (S) to butadiene (B) is (2-3): (7-8).
[0012] More optimally, the model of the styrene-butadiene-styrene is SBS706, a full range of Taiwan, China, and the ratio of S:B is 2:8.
[0013] More optimally, the preparation method of the above-mentioned environmentally friendly aging-resistant adhesive comprises the following steps: taking component A and component B, stirring for 20 to 30 minutes, and obtaining the environmentally friendly aging-resistant adhesive.
[0014] More optimally, the curing conditions of the environmentally friendly aging-resistant adhesive are: irradiation under ultraviolet light (290nm) for 30~60s, curing at 90~100℃ for 2~3h, and curing at 120~140℃ for 3~4h.
[0015] Compared with the prior art, the present invention has the following beneficial effects: (1) no modified fillers or modifiers harmful to human body or environment are added, and the present invention is environmentally friendly; (2) Component A includes a certain proportion of bisphenol A vinyl ester resin, bisphenol A liquid epoxy resin, and cardanol epoxy resin; wherein the vinyl ester resin can form an interpenetrating entangled network with the epoxy resin during curing, thereby promoting stable bonding, optimizing performance and complementing each other, and improving comprehensive performance, but the amount added should not be too much, otherwise the performance will be reduced due to poor compatibility; cardanol epoxy resin, as a diluent, not only plays a diluting role, but also has aliphatic side chains on its molecules to provide excellent water resistance and improve toughness; (3) Component B includes a certain proportion of additive A, additive B, and additive C; additive A includes carboxylated metal organic framework, freeze-dried porous cellulose, and end-hydroxyl silicone oil; the metal organic framework has a highly ordered porous structure and good dispersibility, which can improve the mechanical properties, stability, and chemical properties of epoxy resin, and is loaded with 2-methylimidazole, which can assist in curing; the metal organic framework prepared by the present invention has carboxyl groups on its surface, which can react with the hydroxyl groups of freeze-dried porous cellulose and end-hydroxyl silicone oil to obtain additive A; cellulose is environmentally friendly and has a toughening effect on epoxy resin. After freeze-drying to obtain a porous structure, the dispersibility is further improved and helps to improve the adhesion performance; the end-hydroxyl silicone oil improves the flexibility and weather resistance of epoxy resin and reduces the cracking problem during use; Additive B is lignin containing amino groups and double bonds. The addition of lignin helps to increase the viscosity and can improve the tensile properties and heat-oxidative aging resistance of the epoxy resin. The amino groups and double bonds can participate in curing, improve the self-dispersibility and increase the cross-linking degree of the adhesive. Additive C is SBS with a ratio of S:B of (2-3):(7-8), wherein the rigid segment styrene (S) can improve the strength of the material, and the flexible segment butadiene (B) can improve the flexibility of the material; (4) In summary, the adhesive has good compatibility between the components, good cross-linking degree, good aging resistance and mechanical properties, is not prone to cracking during use, and meets environmental protection standards. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] The following parts are by mass unless otherwise specified; Example 1: S1: Take 4 parts of zinc acetate and 2 parts of copper acetate, add them to 100 parts of water, disperse them evenly with ultrasound, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100°C for 25 hours; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100°C for 24 hours, and dry to obtain an intermediate; take 0.4 parts of 2-methylimidazole, add it to 120 parts of ethanol, disperse it evenly with ultrasound, add 1.5 parts of the intermediate, stir at a uniform speed for 48 hours, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 12 parts of carboxylated metal organic framework, 3 parts of freeze-dried porous cellulose, 5 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 2 parts of lignin in a three-necked flask, add 50 parts of dichloromethane and 4 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 12 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 12 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 4 parts of diethylenetriamine dropwise, stir evenly, add 14 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 12 parts of bisphenol A vinyl ester resin, 50 parts of bisphenol A liquid epoxy resin, and 8 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 18 parts of amine curing agent, 13 parts of additive A, 3 parts of additive B, 0.5 parts of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0018] Example 2: S1: Take 3 parts of zinc acetate and 3 parts of copper acetate, add them to 100 parts of water, disperse them evenly with ultrasound, add 4 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100°C for 25 hours; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100°C for 24 hours, and dry to obtain an intermediate; take 0.3 parts of 2-methylimidazole, add it to 120 parts of ethanol, disperse it evenly with ultrasound, add 1 part of the intermediate, stir at a uniform speed for 48 hours, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 12 parts of carboxylated metal organic framework, 3 parts of freeze-dried porous cellulose, 4 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 1 part of lignin in a three-necked flask, add 40 parts of dichloromethane and 3 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 10 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 10 parts of modified lignin, add 2 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 3 parts of diethylenetriamine dropwise, stir evenly, add 10 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 10 parts of bisphenol A vinyl ester resin, 55 parts of bisphenol A liquid epoxy resin, and 5 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 15 parts of amine curing agent, 15 parts of additive A, 4 parts of additive B, 1 part of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0019] Example 3: S1: Take 4 parts of zinc acetate and 3 parts of copper acetate, add them to 100 parts of water, ultrasonically disperse them evenly, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100°C for 25 hours; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100°C for 24 hours, and dry to obtain an intermediate; take 0.5 parts of 2-methylimidazole, add it to 120 parts of ethanol, ultrasonically disperse it evenly, add 1.5 parts of the intermediate, stir at a uniform speed for 48 hours, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 15 parts of carboxylated metal organic framework, 4 parts of freeze-dried porous cellulose, 6 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 2 parts of lignin in a three-necked flask, add 60 parts of dichloromethane and 6 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 15 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 15 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 5 parts of diethylenetriamine dropwise, stir evenly, add 15 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 15 parts of bisphenol A vinyl ester resin, 55 parts of bisphenol A liquid epoxy resin, and 10 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 20 parts of amine curing agent, 15 parts of additive A, 4 parts of additive B, 1 part of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0020] Comparative Example 1 (the amount of additive A, additive B, and additive C in component B is changed, and the remaining method steps are consistent with Example 1): S1: Take 4 parts of zinc acetate and 2 parts of copper acetate, add them to 100 parts of water, ultrasonically disperse them evenly, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100° C. for 25 hours; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100° C. for 24 hours, and dry to obtain an intermediate; take 0.4 parts of 2-methylimidazole, add it to 120 parts of ethanol, ultrasonically disperse it evenly, add 1.5 parts of the intermediate, stir at a uniform speed for 48 hours, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 12 parts of carboxylated metal organic framework, 3 parts of freeze-dried porous cellulose, 5 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 2 parts of lignin in a three-necked flask, add 50 parts of dichloromethane and 4 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 12 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 12 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 4 parts of diethylenetriamine dropwise, stir evenly, add 14 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 12 parts of bisphenol A vinyl ester resin, 50 parts of bisphenol A liquid epoxy resin, and 8 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 18 parts of amine curing agent, 8 parts of additive A, 5 parts of additive B, 1.5 parts of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0021] Comparative Example 2 (the amount of additive A, additive B, and additive C in component B is changed, and the remaining method steps are consistent with Example 1): S1: Take 4 parts of zinc acetate and 2 parts of copper acetate, add them to 100 parts of water, ultrasonically disperse them evenly, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100° C. for 25 hours; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100° C. for 24 hours, and dry to obtain an intermediate; take 0.4 parts of 2-methylimidazole, add it to 120 parts of ethanol, ultrasonically disperse it evenly, add 1.5 parts of the intermediate, stir at a uniform speed for 48 hours, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 12 parts of carboxylated metal organic framework, 3 parts of freeze-dried porous cellulose, 5 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 2 parts of lignin in a three-necked flask, add 50 parts of dichloromethane and 4 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 12 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 12 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 4 parts of diethylenetriamine dropwise, stir evenly, add 14 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 12 parts of bisphenol A vinyl ester resin, 50 parts of bisphenol A liquid epoxy resin, and 8 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 18 parts of amine curing agent, 16 parts of additive A, 1 part of additive B, 0.1 parts of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0022] Comparative Example 3 (the amount of each raw material added in component A is changed, and the other method steps are consistent with Example 1): S1: Take 4 parts of zinc acetate and 2 parts of copper acetate, add them to 100 parts of water, ultrasonically disperse them evenly, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, condense and reflux at 100°C for 25h; centrifuge and wash, dry the material deposited in the centrifuge tube, add 120 parts of methanol, activate and treat at 100°C for 24h, and dry to obtain an intermediate; take 0.4 parts of 2-methylimidazole, add it to 120 parts of ethanol, ultrasonically disperse it evenly, add 1.5 parts of the intermediate, stir at a uniform speed for 48h, and remove ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S2: Take 10 parts of microfibrillated cellulose and 60 parts of water, disperse them uniformly by ultrasonication, and freeze-dry them to obtain freeze-dried porous cellulose; S3: Take 12 parts of carboxylated metal organic framework, 3 parts of freeze-dried porous cellulose, 5 parts of terminal hydroxyl silicone oil, and 0.15 parts of zinc sulfate, add 60 parts of a mixed solution of water and ethanol, mix well, pressurize and heat to 110° C. in a closed reactor, react for 10 hours, remove the mixed solvent, and obtain additive A; S4: Take 2 parts of lignin in a three-necked flask, add 50 parts of dichloromethane and 4 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 12 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 12 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 4 parts of diethylenetriamine dropwise, stir evenly, add 14 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S5: Take 20 parts of bisphenol A vinyl ester resin, 45 parts of bisphenol A liquid epoxy resin, and 5 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 18 parts of amine curing agent, 13 parts of additive A, 3 parts of additive B, 0.5 parts of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0023] Comparative Example 4 (using a carboxylated metal organic framework as additive A, and the remaining steps are consistent with Example 1): S1: Take 4 parts of zinc acetate and 2 parts of copper acetate, add them to 100 parts of water, and disperse them evenly by ultrasonication, add 6 parts of pyromellitic acid, stir to dissolve, add 70 parts of glacial acetic acid, stir evenly, and condense and reflux at 100° C. for 25 hours; centrifuge and wash, dry the substance deposited in the centrifuge tube, add 120 parts of methanol, activate at 100° C. for 24 hours, and dry to obtain an intermediate; take 0.4 parts of 2-methylimidazole, add it to 120 parts of ethanol, and disperse it evenly by ultrasonication, add 1.5 parts of the intermediate, stir at a uniform speed for 48 hours, and remove the ethanol by rotary evaporation to obtain additive A; S2: Take 2 parts of lignin in a three-necked flask, add 50 parts of dichloromethane and 4 parts of triethylamine under nitrogen atmosphere, stir evenly, ultrasonicate for 3 hours, add 12 parts of acryloyl chloride dropwise within 1 hour, stir at 40°C for 24 hours, add 15 parts of ethanol, stir for 3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Take 12 parts of modified lignin, add 3 parts of polyethylene glycol and NaOH aqueous solution, stir evenly, add 4 parts of diethylenetriamine dropwise, stir evenly, add 14 parts of formaldehyde aqueous solution dropwise, stir and react at 95°C for 4 hours, pour the reaction product into water for precipitation, wash, filter and dry to obtain additive B; S3: Take 12 parts of bisphenol A vinyl ester resin, 50 parts of bisphenol A liquid epoxy resin, and 8 parts of cardanol epoxy resin, and mix them evenly to obtain component A; take 18 parts of amine curing agent, 13 parts of additive A, 3 parts of additive B, 0.5 parts of additive C, and 0.01 parts of photoinitiator, and mix them evenly to obtain component B.
[0024] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); photoinitiator (photoinitiator 1173, CAS: 7473-98-5); zinc acetate (S48372, Shanghai Yuanye); copper acetate (S42613, Shanghai Yuanye); pyromellitic acid (CAS: 89-05-4); glacial acetic acid (CAS: 64-19-7); methanol (CAS: 67-56-1); 2-methylimidazole (CAS: 693-98-1); microfibrillated cellulose (210609145917, Kramar); hydroxyl-terminated silicone oil (dual-terminated hydroxyl silicone oil IOTA21 10, Anhui Aiyota Silicone Oil Co., Ltd.); zinc sulfate (S22124, Shanghai Yuanye); lignin (No. 6875, Wuhan Xinxin Jiali Biotechnology Co., Ltd.); dichloromethane (CAS: 75-09-2); triethylamine (CAS: 121-44-8); acryloyl chloride (CAS: 814-68-6); polyethylene glycol (polyethylene glycol 400, Shandong Xinheng Chemical Co., Ltd.); diethylenetriamine (CAS: 111-40-0); bisphenol A type vinyl ester resin 854 (Shanghai Fuchen Chemical Co., Ltd.); bisphenol A type liquid epoxy resin E51 (Jinan Shanhai Chemical Technology Co., Ltd.); cardanol epoxy resin NC-513 (Cardolite); 4,4-diaminodiphenyl sulfone (CAS: 80-08-0).
[0025] Experiment: Take component A and component B prepared in Examples 1 to 3 and Comparative Examples 1 to 4, stir for 25 minutes, and obtain a sample; (1) Used to bond LY12CZ aluminum test piece, irradiate under ultraviolet light (290nm) for 45s, cure at 100℃ for 2h, cure at 120℃ for 4h, cool to room temperature, refer to GB / T 7124-2008 standard, test shear strength, and the test speed is 15mm / min; (2) High temperature heat aging at 177℃ for 100h, cool to room temperature, and test shear strength after heat aging; (3) Take a sample, irradiate under ultraviolet light (290nm) for 45s, cure at 100℃ for 2h, cure at 120℃ for 4h, cool to room temperature, refer to GB / T 1040.3-2006 standard, and test elongation at break; specific data are shown in the table below; Conclusion: Comparative Examples 1 and 2 changed the amount of additive A, additive B, and additive C added in component B, and the performance was not as good as that in the embodiment, from which it can be seen that the amount of additives added needs to be controlled; Comparative Example 3 changed the amount of each raw material added in component A, and the performance decreased, from which it can be seen that the amount of bisphenol A vinyl ester resin, bisphenol A liquid epoxy resin, and cardanol epoxy resin added is also of great significance; Comparative Example 4 uses a carboxylated metal organic framework as additive A, that is, no freeze-dried porous cellulose and terminal hydroxyl silicone oil are added, and the performance decreases significantly; in summary, component A and component B prepared by the present invention can produce an adhesive with good bonding performance, good mechanical properties, and good aging resistance, and meets environmental protection requirements.
[0026] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. An environmentally friendly and aging-resistant adhesive, characterized in that: It comprises component A and component B; the component A comprises the following raw materials, calculated by weight: 10 to 15 parts of bisphenol A type vinyl ester resin, 45 to 55 parts of bisphenol A type liquid epoxy resin, and 5 to 10 parts of cardanol epoxy resin; The component B comprises the following raw materials, calculated by weight: 15-20 parts of amine curing agent, 12-15 parts of additive A, 3-4 parts of additive B, 0.5-1 parts of additive C, and 0.01-0.02 parts of photoinitiator; The additive A is a metal organic framework loaded with a curing agent; the additive B is lignin containing an amino group and a double bond; and the additive C is styrene-butadiene-styrene.
2. The environmentally friendly anti-aging adhesive according to claim 1, characterized in that: The preparation of the additive A is specifically The following steps are involved: S1: Take zinc acetate and copper acetate, add them into water and disperse them evenly by ultrasonication, add pyromellitic acid, stir to dissolve, add glacial acetic acid, stir evenly, condense and reflux, centrifuge and wash, dry the material deposited in the centrifuge tube, add methanol for activation treatment, and dry to obtain an intermediate; S2: Take 2-methylimidazole and add it to ethanol, mix it by ultrasonication, add the intermediate, stir it at a constant speed, and remove the ethanol by rotary evaporation to obtain a carboxylated metal organic framework; S3: Take the carboxylated metal organic framework, freeze-dried porous cellulose, terminal hydroxyl silicone oil and zinc sulfate, add them to a mixed solution of water and ethanol, mix them evenly, pressurize and heat to 110-120°C to react for 8-10 hours, remove the mixed solvent, and obtain additive A.
3. The environmentally friendly anti-aging adhesive according to claim 2, characterized in that: The intermediate comprises the following raw materials, calculated by weight: 3-4 parts of zinc acetate, 2-3 parts of copper acetate, 100-120 parts of water, 4-6 parts of pyromellitic acid, 65-70 parts of glacial acetic acid, and 100-120 parts of methanol; The carboxylated metal organic framework comprises the following raw materials, calculated by weight: 0.3-0.5 parts of 2-methylimidazole, 100-120 parts of ethanol, and 1-1.5 parts of an intermediate; The additive A comprises the following raw materials, calculated by weight: 12-15 parts of carboxylated metal organic framework, 3-4 parts of freeze-dried porous cellulose, 4-6 parts of terminal hydroxyl silicone oil, 0.1-0.2 parts of zinc sulfate, and 50-60 parts of a mixed solution of water and ethanol.
4. The environmentally friendly anti-aging adhesive according to claim 2, characterized in that: The preparation of the freeze-dried porous cellulose specifically includes the following steps: taking microfibrillated cellulose and water, uniformly dispersing by ultrasonication, and freeze-drying to obtain freeze-dried porous cellulose; the mass ratio of microfibrillated cellulose to water is 1:(5-6).
5. The environmentally friendly anti-aging adhesive according to claim 1, characterized in that: The preparation of the additive B specifically includes the following steps: Step 1: Take lignin, add dichloromethane and triethylamine under the protection of nitrogen atmosphere, stir evenly, ultrasonicate for 2-3 hours, drop acryloyl chloride, stir at 40-45° C. for 20-24 hours, add ethanol and stir for 2-3 hours, wash with water, filter under reduced pressure, and dry to obtain modified lignin; Step 2: Take modified lignin, polyethylene glycol, and NaOH aqueous solution, stir evenly, add diethylenetriamine dropwise, stir evenly, add formaldehyde aqueous solution dropwise, react at 90-95°C for 3-4h, pour the reaction product into water for precipitation, wash, filter, and dry to obtain additive B.
6. The environmentally friendly anti-aging adhesive according to claim 5, characterized in that: The modified lignin includes the following raw materials, calculated by weight: 1-2 parts of lignin, 40-60 parts of dichloromethane, 3-6 parts of triethylamine, 10-15 parts of acryloyl chloride, and 10-15 parts of ethanol; The additive B comprises the following raw materials, calculated by weight: 10-15 parts of modified lignin, 2-3 parts of polyethylene glycol, 3-5 parts of diethylenetriamine, and 10-15 parts of formaldehyde aqueous solution with a formaldehyde concentration of 37 wt%; the NaOH aqueous solution comprises 0.01-0.02 parts of NaOH and 10-15 parts of water.
7. The environmentally friendly anti-aging adhesive according to claim 1, characterized in that: In the styrene-butadiene-styrene, the ratio of styrene to butadiene is (2-3): (7-8).
8. The method for preparing an environmentally friendly aging-resistant adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: Take component A and component B, stir for 20 to 30 minutes, and obtain an environmentally friendly and aging-resistant adhesive.
Citation Information
Patent Citations
Vinyl ester resin modified epoxy pouring sealant and preparation method thereof
CN103059515A
Epoxy resin curing agent and preparation method thereof
CN114409874A
Epoxy resin adhesive and preparation method thereof
CN114539959A
High-strength weather-resistant automobile structure adhesive and preparation method thereof
CN115160966A
Black liquor lignin-based epoxy resin film composite material and preparation method thereof
CN116515142A